PERANAN MOTOR LISTRIK DC PADARANCANG BANGUN PEMBERIAN PAKAN TERNAK AYAM BERBASIS PROGRAMMABLE LOGIC CONTROLLER (PLC) - -, Djessica; Listiana, Reni (Jurnal Mahasiswa Terapan, 2024)
Feeding chickens is an important aspect of raising chickens which affects the growth and health of livestock. An efficient and automatic feeding system can increase farmer productivity. Automatic feeding with a motor drive system, scheduled feeding is considered more efficient and saves time and physical involvement in feeding livestock. With a motor drive system, the speed and accuracy of the motor for distributing feed are parameters that must be controlled so that the required parameters are met precisely. There is a control technology that is able to meet these parameters with an automation process, namely the Programmable Logic Controller (PLC). The PLC acts as a motor controller so that the parameters that must be met can be achieved effectively and efficiently. In this research, using the Omron CP1L-M60DR-A PLC as the control system, mini DC gearbox as the driver. Testing is carried out with variations in speed and time accuracy. In the test results, data was obtained that to produce the correct speed and time, the motor rotation speed was 17.1 rpm, the feed stopping time from containers 1, 2, and 3 was 6 seconds, and the total travel time was 3 minutes 36 seconds.